Stress Distribution in Bone and Implants in Mandibular 6-Implant-Supported Cantilevered Fixed Prosthesis: A 3D Finite Element Study. Issue 6 (December 2015) - Padhye, Omkar Vinayak; Herekar, Manisha; Patil, Viraj; Mulani, Shahnawaz; Sethi, Megha; Fernandes, Aquaviva
Abstract : Purpose: The purpose of the study was to evaluate by a 3-dimensional finite element analysis the load transmission to periimplant bone by a framework supported by 6 implants placed in an edentulous mandible and to compare the stress distribution for varying cantilever lengths. Methodology: A computerized model of the anterior segment of a mandible with a 6-implant-supported bridge was created in software. The length of the cantilever segment was considered as 10, 15, and 20 mm. A 150 N load was applied to the terminal point of the cantilever segment, and Von Mises stresses were analyzed along implants, framework, and bone. Results: When the cantilever length was increased from 10 to 20 mm, the stress increased 79.66% in the framework, 68.16% in implants, and 59.96% and 52.81% in cortical and cancellous bones, respectively. Conclusion: The greatest amount of stress was seen around the distal-most region of the distal-most implant. The framework absorbed the maximum amount of stresses followed by the implants, cortical bone, and cancellous bone. Extension of the cantilever beyond 15 mm could lead to greater stress in the lingual cortical plate, which could compromise the integrity of the implants.